Fontes de custeio do sistema sindical - Sanchez, Suelen Alves (2017)
This study deals with the sources of funding of the Brazilian trade union system, established decades ago in the Brazilian legal system and approved by the Constitution of 1988, with the purpose of clearly and objectively addressing the actual intention of the legislator for each type of union contribution today in place: union contribution, confederation contribution, assistance contribution and associative contribution. Firstly, this work is based on the principles enshrined in the Constitution, in the legislation in general, in the vast legal literature of renowned jurists on the subject and, finally, in a jurisprudential historical. From a social point of view, as will be seen, it is noted that the subject in question enjoys a certain antipathy on the part of the represented ones; from a legal point of view, it is far from settled, starting with a doctrine with diverging understandings regarding the legal nature of the kinds of mentioned trade union contributions. A range of doctrinal fundamentals in the most varied senses and of great persuasion, end up serving as the basis for lawsuits, also generating, opposite decisions, sometimes in the same court of justice. As such, confusion takes place. In this scenario, full of contradictions, rests clear the need for a reform in the current trade union system that could promote the settling of the subject, an idea defended in the conclusive phase of this work. However, such a change is uncertain, in spite of the bills in progress in the legislative houses, on which this study takes positions, which at certain moments will be opposed to the theses of highly renowned jurists